Wnt signaling pathway inhibitors, sclerostin and DKK-1, correlate with pain and bone pathology in patients with Gaucher disease - Ivanova, Margarita M.; Dao, Julia; Kasaci, Neil; Friedman, Andrew; Noll, Lauren; Goker-Alpan, Ozlem (Frontiers in Endocrinology, 2022)
Patients with Gaucher disease (GD) have progressive bone involvement that clinically presents with debilitating bone pain, structural bone changes, bone marrow infiltration (BMI), Erlenmeyer flask (EM) deformity, and osteoporosis. Pain is referred by the majority of GD patients and continues to persist despite the type of therapy. The pain in GD is described as chronic deep penetrating pain; however, sometimes, patients experience severe acute pain. The source of bone pain is mainly debated as nociceptive pain secondary to bone pathology or neuropathic or inflammatory origins. Osteocytes constitute a significant source of secreted molecules that coordinate bone remodeling. Osteocyte markers, sclerostin (SOST), and dickkopf-1 (DKK-1), inactivate the canonical Wnt signaling pathway and leads to inhibition of bone formation. Thus, circulated SOST and DKK-1 are potential biomarkers of skeletal abnormalities. This study aimed to assess the circulating level of SOST and DKK-1 in patients with GD and its correlation with clinical bone pathology parameters: pain, BMI, EM deformity, and bone mineral density. 39 GD patients were classified into cohorts based on the presence and severity of bone manifestations. Serum levels of SOST, and DKK-1 were quantified by enzyme-linked immunosorbent assays. The highest level of SOST was measured in GD patients with pain, BMI, and EM deformity. The multiparameter analysis demonstrated that 95% of GD patients with pain, BMI, and EM deformity had increased levels of SOST. The majority of patients with elevated SOST also have osteopenia or osteoporosis. A Pearson linear correlation analysis showed a positive correlation between serum DKK-1 and SOST in healthy controls and GD patients with normal bone mineral density. However, the balance between SOST and DKK-1 waned in GD patients with osteopenia or osteoporosis. Conclusion. The osteocyte marker, SOST, when elevated, is associated with bone pain, BMI, and EM flask deformity in GD patients. The altered SOST and DKK-1 ratio correlate with the reduction of bone mineral density. These data confirm that the Wnt signaling pathway plays a role in GD-associated bone disease. SOST and bone pain could be used as biomarkers to assess patients with a high risk of BMI and EM flask deformities.